Haemophilia registry of the Medical Committee of the Swiss Hemophilia Society - von der Weid, N. (Hämostaseologie, 2012)
The Haemophilia Registry of the Swiss Haemo philia Society was created in the year 2000. The latest records from October 31st 2011 are presented here. Included are all patients with haemophilia A or B and other inherited coagulation disorders (including VWD patients with R-Co activity below 10%) known and followed by the 11 paediatric and 12 adult haemophilia treatment or reference centers. Currently there are 950 patients registered, the majority of which (585) having haemophilia A. Disease severity is graded according to ISTH criteria and its distribution between mild, moderate and severe haemophilia is similar to data from other European and American registries. The majority (about two thirds) of Swiss patients with haemophilia A or B are treated on-demand, with only about 20% of patients being on prophylaxis. The figure is different in paediatrics and young adults (1st and 2nd decades), where 80 to 90% of patients with haemophilia A are under regular prophylaxis. Interestingly enough, use of factor concentrates, although readily available, is rather low in Switzerland, especially when taking the country’s GDP into account: The total amount of factor VIII and IX was 4.94 U pro capita, comparable to other European countries with distinctly lower incomes (Poland, Slovakia, Hungary). This finding is mainly due to the afore mentioned low rate of prophylactic treatment of haemophilia in our country. Our registry remains an important instrument of quality control of haemophilia therapy in Switzerland.
Keywords: Haemophilia; registry; epidemiology; quality control; Switzerland